EDucation & GEnder Gender-specific education in different countries. Historical aspects - current trends - Holz, Oliver; Shelton, Fiona (Waxmann Verlag, 2013)
A study funded by the European Commission, relating to gender specific differences in learning achievements, shows among other things that whilst gender equality is a hot topic in many countries a general equality policy is not always advocated. More importantly, measures to reduce gender differences in achievement seem to focus primarily on the underachievement of boys. In this publication, historical aspects and current trends within 12 European countries, regarding gender equality in education are presented and compared. The country studies and comparative analysis will inform and inspire everybody who is interested in gender issues in education.